A new Afrolimnophila Alexander from Europe (Diptera: Limoniidae) - Starý, Jaroslav; Kolcsár, Levente-Péter (Zootaxa, 2021)
A new species of the genus Afrolimnophila Alexander, 1956 is described from Europe, A. erhanae sp. nov., and its wing and male terminalia are illustrated. A key to West Palearctic species of the genus is appended.